Effect of Tomato, Beetroot and Carrot Juice Addition on Physicochemical, Antioxidant and Texture Properties of Wheat Bread - Marianna Raczyk; Bartosz Kruszewski; Ewa Zachariasz (MDPI AG, 2022)
Bakery products, including bread, are important components of the diet of people all over the world. One of the food industry's goals is to improve its quality in the context of healthiness and physical parameters. Consumers' perception of sensory quality is an important aspect of food choice. Thus, the study aimed to enhance nutritional parameters (antioxidant capacity, content of phenolic compounds) together with maintaining or increasing bread quality (texture, color, volume and sensory properties). Among vegetable juices, tomato, beetroot and carrot were selected, as they are easily accessible in Europe and are inexpensive. At the same time, those juices are known to be high in antioxidants. In this study, the effect of substituting recipe water with tomato, beetroot and carrot juices (replacement level: 15, 30, 50% v/v) was evaluated in terms of the specific volume, texture, color, acidity, polyphenol contents, antioxidant and sensory properties. It was concluded that juice content had a significant positive impact on physicochemical parameters such as volume, color, acidity, as well as the antioxidant activity of breads. The carrot and beetroot juices were the most efficient in terms of shaping wheat bread properties, especially in terms of antioxidant activity.